Knowledge and practice of hygiene in BRAC's WASH Programme areas - Akter, Tahera; Ali, ARM Mehrab (BRAC Research and Evaluation Division (RED), 2019)
Improved hygiene behaviour is one of the most effective means of reducing disease occurrence. However, question may arise, which factors did contribute to such improvement? Past studies seldom addressed these issues systematically nor explained the influencing factors that facilitate or impede hygiene knowledge and practice from the perspectives of successful and unsuccessful households. This study, combining qualitative and quantitative methods, measured the changes in knowledge and practice of hygiene and explored factors that facilitate or impede hygiene behaviours in water, sanitation and hygiene (WASH) intervention areas of BRAC. Indepth interviews were conducted with 144 purposively selected women. Some of their practices were physically verified to get the proof of their claims. Besides, 30,000 systematically chosen households studied in the baseline were revisited in the midline survey for collecting quantitative data. Results on common variables investigated through both quantitative and qualitative approaches were triangulated. Findings show that respondent's hygiene behaviours were mainly facilitated by improved knowledge and awareness about health and environment-related issues. BRAC's financial assistance had positive impact on latrine ownership resulting in increased privacy and dignity of the households. Latrine or tubewell ownership also increased their social prestige and sense of responsibility. In this regard, maintaining hygiene behaviours for healthy life was perceived as everybody's responsibility. On the other hand, lack of interest in attending cluster meeting, traditional knowledge, poverty, difficulties in carrying water, location of latrine, lack of will to practice, and complex mind-set were the impeding factors to hygiene knowledge and practice. Mainly the psychosocial aspects made the difference between successful and unsuccessful households, as successful households followed hygiene behaviours irrespective of poverty and other barriers. To increase awareness to a further extent and to transform knowledge into practice and practice into habit, more cluster meetings ensuring participation of all including children and home visits by the programme organizers are imperative.